Bridging the Energy Balance Gap in Eddy‐Covariance Measurements: Insights From Standardized Network Data - Giacomo Nicolini; David Durden; Luca Di Fiore; Christopher Florian; Simone Sabbatini; Bert Gielen; Arne Iserbyt; Benjamin Loubet; Ivan Mammarella; Adriana Mariotti; Maarten Op de Beeck; Caleb Slemmons; et al. (Global Change Biology, 2026)
The lack of energy balance closure in Eddy‐Covariance (EC) measurements is a well‐known, still unresolved challenge in micrometeorology, with energy balance closure (EBC) rates typically ranging between 60% and 80%. While numerous hypotheses have been proposed to explain this imbalance, the relative contributions of neglected energy storage terms, data quality and flux processing options remain insufficiently disentangled. Using standardized ICOS and NEON datasets, we show that a significant portion of the observed energy imbalance can be attributed to overlooked or inconsistently handled energy components and turbulent flux quality control. Using data drawn from 84 sites, we show that comprehensive energy accounting—including soil heat flux, storage terms (soil, air, biomass), photosynthetic energy demand, and strict quality filtering of turbulent fluxes—improved EBC by 16% on average, with site‐specific gains up to 40%. However, we also identify a persistent residual imbalance that is unlikely to be resolved through methodological refinements or additional measurements alone, pointing to fundamental physical processes that are not accounted for in the standard measurement and processing. We argue that this unresolved imbalance should be explicitly acknowledged and bounded, rather than implicitly absorbed into correction schemes, and we outline practical guidance for diagnosing and interpreting EBC in standardized flux networks. This perspective evaluates methodological advances and residual uncertainties, providing an actionable framework for the appropriate use of EC energy fluxes in carbon, water, and climate research.

Opening Pandora’s box: First insights into the genetic diversity of Aphanomyces astaci in Switzerland - Simone Roberto Rolando Pisano; Eliane Jemmi; Jonas Steiner; Elodie Cristina; Regula Hirschi; Zoé Delefortrie; Gary Delalay; Heike Schmidt-Posthaus (Journal of Invertebrate Pathology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Developing a conceptual framework for interdisciplinary communication, collaboration, and integration: A structured approach - Jialin Zhang; Hanna Salomon; Martin Nicola Huber; Harald Bugmann; Julie Elisabet Dölker; Louis König; Jasmin Krähenbühl; Eva Lieberherr; Ivana Logar; Brian McArdell; Peter Molnar; Simone Quatrini; et al. (Ambio, 2025)
Interdisciplinary research is essential to address the complex environmental challenges faced by social-ecological systems (SES). However, it is often hindered by difficulties in integrating diverse knowledge and perspectives. Conceptual Frameworks (CFs) can act as boundary objects, facilitating integration in contexts with incomplete knowledge, nonlinearity, and divergent interests. Yet, guidance on developing CFs remains limited. To address this gap, we develop a structured approach and apply it within a research project focused on enhancing the resilience of Swiss Alpine ecosystems. Our approach includes three phases: (1) defining boundary concepts, (2) developing a CF as a boundary object, and (3) using the CF as a boundary object. The resulting CF supports communication, collaboration, and integration across disciplines, advancing SES research that addresses ecological resilience and sustainability. Our approach can be used by other interdisciplinary teams aiming to develop adaptable CFs that facilitate knowledge integration across disciplines.

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Borealisation of Plant Communities in the Arctic Is Driven by Boreal‐Tundra Species - Mariana García Criado; Isabel C. Barrio; James D. M. Speed; Anne D. Bjorkman; Sarah C. Elmendorf; Isla H. Myers‐Smith; Rien Aerts; Juha M. Alatalo; Katlyn R. Betway‐May; Robert G. Björk; Mats P. Björkman; Daan Blok; et al. (Ecology Letters, 2025)
Following rapid climate change, tundra plant communities are experiencing extensive compositional shifts. A conservation concern is the potential encroachment of boreal species into the tundra (‘borealisation’). Tundra borealisation has been sporadically reported, but not systematically quantified. Here, we synthesised data from across 32 study areas, spanning 1137 plots and 287 vascular plant species, resurveyed between 1981 and 2023. We (i) quantified tundra borealisation as the colonisation and increase in abundance of Boreal and Boreal‐Tundra species, (ii) assessed biogeographical, climatic and local borealisation drivers and (iii) identified species contributing to borealisation and their associated traits. Half of the plots experienced borealisation, although borealisation rates were not different to random expectation. Borealisation was greater in Eurasia, closer to the treeline, at higher elevations, in warmer and wetter regions, where climate change was limited, and where initial boreal abundance was lower. Boreal coloniser species were generally short‐statured, and more often shrubs and graminoids. Boreal species colonised around three times less frequently than Boreal‐Tundra species. Hence, our findings indicate that tundra borealisation is mainly driven by the spread of already established boreal‐low Arctic tundra species. These plant community composition changes could have cascading impacts on land‐atmosphere interactions, trophic dynamics and Indigenous and local livelihoods.

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Differentially expressed messenger RNA isoforms in beef cattle skeletal muscle with different fatty acid profiles - Bruna Maria Salatta; Maria Malane Magalhães Muniz; Larissa Fernanda Simielli Fonseca; Lucio Flavio Macedo Mota; Caio de Souza Teixeira; Gabriela Bonfá Frezarim; Marta Serna-García; Leonardo Machestropa Arikawa; Patrícia Iana Schmidt; Sindy Liliana Caivio Nasner; Danielly Beraldo dos Santos Silva; Angélica Simone Cravo Pereira; et al. (Meat Science, 2025)

Impact of physicochemical parameters on nicotine metabolites and Bisphenol A in municipal wastewater: A pilot study in a German metropolitan area - Dennis Schmiege; Amir Salemi; Christian Högel; Simone Bettinger; Torsten C. Schmidt; Susanne Moebus (Science of The Total Environment, 2025)

Timing and origin of the post-collisional Venda Nova and Várzea Alegre Plutons from the Araçuaí belt, Espírito Santo, Brazil - Clara Talca Onken; Jessica Eberhard-Schmid; Livia Hauser; Simone Marioni; Andrea Galli; Valdecir de Assis Janasi; Max W. Schmidt (Lithos, 2024)

An old unknown: 40 years of crayfish plague monitoring in Switzerland, the water tower of Europe - Simone Roberto Rolando Pisano; Jonas Steiner; Elodie Cristina; Zoé Delefortrie; Gary Delalay; Raphael Krieg; Armin Zenker; Heike Schmidt-Posthaus (Journal of Invertebrate Pathology, 2024)

Evaluation of the point sampling method and inter-comparison of remote emission sensing systems for screening real-world car emissions - Markus Knoll; Martin Penz; Christina Schmidt; Denis Pöhler; Tommaso Rossi; Simone Casadei; Yoann Bernard; Ǻsa M. Hallquist; Ǻke Sjödin; Alexander Bergmann (Science of The Total Environment, 2024)

Effects of the nerve agent VX on hiPSC-derived motor neurons - Catherine Schaefers; Wolfgang Schmeißer; Harald John; Franz Worek; Theo Rein; Simone Rothmiller; Annette Schmidt (Archives of Toxicology, 2024)
Poisoning with the organophosphorus nerve agent VX can be life-threatening due to limitations of the standard therapy with atropine and oximes. To date, the underlying pathomechanism of VX affecting the neuromuscular junction has not been fully elucidated structurally. Results of recent studies investigating the effects of VX were obtained from cells of animal origin or immortalized cell lines limiting their translation to humans. To overcome this limitation, motor neurons (MN) of this study were differentiated from in-house feeder- and integration-free-derived human-induced pluripotent stem cells (hiPSC) by application of standardized and antibiotic-free differentiation media with the aim to mimic human embryogenesis as closely as possible. For testing VX sensitivity, MN were initially exposed once to 400 µM, 600 µM, 800 µM, or 1000 µM VX and cultured for 5 days followed by analysis of changes in viability and neurite outgrowth as well as at the gene and protein level using µLC-ESI MS/HR MS, XTT, IncuCyte, qRT-PCR, and Western Blot. For the first time, VX was shown to trigger neuronal cell death and decline in neurite outgrowth in hiPSC-derived MN in a time- and concentration-dependent manner involving the activation of the intrinsic as well as the extrinsic pathway of apoptosis. Consistent with this, MN morphology and neurite network were altered time and concentration-dependently. Thus, MN represent a valuable tool for further investigation of the pathomechanism after VX exposure. These findings might set the course for the development of a promising human neuromuscular test model and patient-specific therapies in the future.

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Detection of novel RNA viruses in wild noble crayfish (Astacus astacus): A virome analysis in Swiss water bodies - Tatiana Zingre; Simone Roberto Rolando Pisano; Nicole Wildi; Kara Lynne Dianne Dawson; Elodie Cristina; Torsten Seuberlich; Heike Schmidt-Posthaus (Journal of Invertebrate Pathology, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

A pragmatic authenticity assessment of lemon (Citrus limon [L.] Burm.f.) juices by its profile of coumarins, psoralens, and polymethoxyflavones - Markus Jungen; Nenad Dragićević; Miriam Rodriguez-Werner; Simone Schmidt; Katy Dinis; Lucie Tsamba; Eric Jamin; Thorsten Fiedler; Nadine Fischbach; Christof B. Steingass; Valérie Camel; Ralf Schweiggert (Food Control, 2023)

Disentangling drivers of litter decomposition in a multi-continent network of tree diversity experiments - Ellen Desie; Juan Zuo; Kris Verheyen; Ika Djukic; Koenraad Van Meerbeek; Harald Auge; Nadia Barsoum; Christel Baum; Helge Bruelheide; Nico Eisenhauer; Heike Feldhaar; Olga Ferlian; et al. (Science of The Total Environment, 2023)

Sulfur mustard single-dose exposure triggers senescence in primary human dermal fibroblasts - Gabriele Horn; Catherine Schäfers; Horst Thiermann; Sandra Völkl; Annette Schmidt; Simone Rothmiller (Archives of Toxicology, 2022)
Chronic wounds, skin blisters, and ulcers are the result of skin exposure to the alkylating agent sulfur mustard (SM). One potential pathomechanism is senescence, which causes permanent growth arrest with a pro-inflammatory environment and may be associated with a chronic wound healing disorder. SM is known to induce chronic senescence in human mesenchymal stem cells which are subsequently unable to fulfill their regenerative function in the wound healing process. As dermal fibroblasts are crucial for cutaneous wound healing by being responsible for granulation tissue formation and synthesis of the extracellular matrix, SM exposure might also impair their function in a similar way. This study, therefore, investigated the SM sensitivity of primary human dermal fibroblasts (HDF) by determining the dose–response curve. Non-lethal concentrations LC 1 (3 µM) to LC 25 (65 µM) were used to examine the induction of senescence. HDF were exposed once to 3 µM, 13 µM, 24 µM, 40 µM or 65 μM SM, and were then cultured for 31 days. Changes in morphology as well as at the genetic and protein level were investigated. For the first time, HDF were shown to undergo senescence in a time- and concentration-dependent manner after SM exposure. They developed a characteristic senescence phenotype and expressed various senescence markers. Proinflammatory cytokines and chemokines were significantly altered in SM-exposed HDF as part of a senescence-associated secretory phenotype. The senescent fibroblasts can thus be considered a contributor to the SM-induced chronic wound healing disorder and might serve as a new therapeutic target in the future.

Correction to: Prevalence and patient‑rated relevance of complexity factors in medication regimens of community dwelling patients with polypharmacy - Viktoria S. Wurmbach; Steffen J. Schmidt; Anette Lampert; Simone Bernard; Andreas D. Meid; Eduard Frick; Michael Metzner; Stefan Wilm; Achim Mortsiefer; Bettina Bücker; Attila Altiner; Lisa Sparenberg; et al. (European Journal of Clinical Pharmacology, 2022)

Prevalence and patient-rated relevance of complexity factors in medication regimens of community-dwelling patients with polypharmacy - Viktoria S. Wurmbach; Steffen J. Schmidt; Anette Lampert; Simone Bernard; Andreas D. Meid; Eduard Frick; Michael Metzner; Stefan Wilm; Achim Mortsiefer; Bettina Bücker; Attila Altiner; Lisa Sparenberg; et al. (European Journal of Clinical Pharmacology, 2022)
Purpose To describe the prevalence of complexity factors in the medication regimens of community-dwelling patients with more than five drugs and to evaluate the relevance of these factors for individual patients. Methods Data were derived from the HIOPP-6 trial, a controlled study conducted in 9 general practices which evaluated an electronic tool to detect and reduce complexity of drug treatment. The prevalence of complexity factors was based on the results of the automated analysis of 139 patients’ medication data. The relevance assessment was based on the patients’ rating of each factor in an interview (48 patients included for analysis). Results A median of 5 (range 0–21) complexity factors per medication regimen were detected and at least one factor was observed in 131 of 139 patients. Almost half of these patients found no complexity factor in their medication regimen relevant. Conclusion In most medication regimens, complexity factors could be identified automatically, yet less than 15% of factors were indeed relevant for patients as judged by themselves. When assessing complexity of medication regimens, one should especially consider factors that are both particularly frequent and often challenging for patients, such as use of inhalers or tablet splitting. Trial registration The HIOPP-6 trial was registered retrospectively on May 17, 2021, in the German Clinical Trials register under DRKS-ID DRKS00025257.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Indigenous and local communities can boost seed supply in the UN decade on ecosystem restoration - Danilo Urzedo; Simone Pedrini; Daniel L. M. Vieira; Alexandre B. Sampaio; Bruna D. F. Souza; Eduardo Malta Campos-Filho; Fatima C. M. Piña-Rodrigues; Isabel B. Schmidt; Rodrigo G. P. Junqueira; Kingsley Dixon (Ambio, 2022)
The UN Decade of Ecosystem Restoration is poised to trigger the recovery of ecosystem services and transform structural injustices across the world in a way unparalleled in human history. The inclusion of diverse Indigenous and local communities to co-create robust native seed supply systems is the backbone to achieve the goals for the Decade. Here we show how community-based organizations have co-developed native seed supply strategies for landscape restoration from the bottom-up. We draw on the interconnections over two decades of seed networks in Brazil and the emerging Indigenous participation in native seed production in Australia. From an environmental justice perspective, we provide a participatory seed supply approach for local engagement, noting local geographical, social and cultural contexts. Meeting large-scale restoration goals requires the connection between local seed production and collaborative platforms to negotiate roles, rights and responsibilities between stakeholders. An enduring native seed supply must include a diversity of voices and autonomy of community groups that builds equitable participation in social, economic, and environmental benefits.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Chronic senescent human mesenchymal stem cells as possible contributor to the wound healing disorder after exposure to the alkylating agent sulfur mustard - Simone Rothmiller; Niklas Jäger; Nicole Meier; Thimo Meyer; Adrian Neu; Dirk Steinritz; Horst Thiermann; Michael Scherer; Christoph Rummel; Aswin Mangerich; Alexander Bürkle; Annette Schmidt (Archives of Toxicology, 2021)
Wound healing is a complex process, and disturbance of even a single mechanism can result in chronic ulcers developing after exposure to the alkylating agent sulfur mustard (SM). A possible contributor may be SM-induced chronic senescent mesenchymal stem cells (MSCs), unable to fulfil their regenerative role, by persisting over long time periods and creating a proinflammatory microenvironment. Here we show that senescence induction in human bone marrow derived MSCs was time- and concentration-dependent, and chronic senescence could be verified 3 weeks after exposure to between 10 and 40 µM SM. Morphological changes, reduced clonogenic and migration potential, longer scratch closure times, differences in senescence, motility and DNA damage response associated genes as well as increased levels of proinflammatory cytokines were revealed. Selective removal of these cells by senolytic drugs, in which ABT-263 showed initial potential in vitro, opens the possibility for an innovative treatment strategy for chronic wounds, but also tumors and age-related diseases.

Individual factors increasing complexity of drug treatment—a narrative review - Steffen J. Schmidt; Viktoria S. Wurmbach; Anette Lampert; Simone Bernard; Walter E. Haefeli; Hanna M. Seidling; Petra A. Thürmann (European Journal of Clinical Pharmacology, 2020)
Purpose Complexity of drug treatment is known to be a risk factor for administration errors and nonadherence promoting higher healthcare costs, hospital admissions and increased mortality. Number of drugs and dose frequency are parameters often used to assess complexity related to the medication regimen. However, factors resulting from complex processes of care or arising from patient characteristics are only sporadically analyzed. Hence, the objective of this review is to give a comprehensive overview of relevant, patient-centered factors influencing complexity of drug treatment. Methods A purposeful literature search was performed in MEDLINE to identify potential complexity factors relating to the prescribed drug (i.e. dosage forms or other product characteristics), the specific medication regimen (i.e. dosage schemes or additional instructions), specific patient characteristics and process characteristics. Factors were included if they were associated to administration errors, nonadherence and related adverse drug events detected in community dwelling adult patients. Results Ninety-one influencing factors were identified: fourteen in “dosage forms”, five in “product characteristics”, twelve in “dosage schemes”, nine in “additional instructions”, thirty-one in “patient characteristics” and twenty in “process characteristics”. Conclusions Although the findings are limited by the non-systematic search process and the heterogeneous results, the search shows the influence of many factors on the complexity of drug treatment. However, to evaluate their relevance for individual patients, prospective studies are necessary.

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Gemcitabine Treatment of Rat Soft Tissue Sarcoma with Phosphatidyldiglycerol-Based Thermosensitive Liposomes - Simone Limmer; Jasmin Hahn; Rebecca Schmidt; Kirsten Wachholz; Anja Zengerle; Katharina Lechner; Hansjörg Eibl; Rolf D. Issels; Martin Hossann; Lars H. Lindner (Pharmaceutical Research, 2014)

Chlorogenic acid, a metabolite identified by untargeted metabolome analysis in resistant tomatoes, inhibits the colonization by Alternaria alternata by inhibiting alternariol biosynthesis - Edyta Wojciechowska; Christoph H. Weinert; Björn Egert; Bernhard Trierweiler; Markus Schmidt-Heydt; Bernd Horneburg; Simone Graeff-Hönninger; Sabine E. Kulling; Rolf Geisen (European Journal of Plant Pathology, 2014)

Comparative neuroanatomy of Caudofoveata, Solenogastres, Polyplacophora, and Scaphopoda (Mollusca) and its phylogenetic implications - Simone Faller; Birgen Holger Rothe; Christiane Todt; Andreas Schmidt-Rhaesa; Rudi Loesel (Zoomorphology, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

An endocannabinoid system is localized to the hypophysial pars tuberalis of Syrian hamsters and responds to photoperiodic changes - Shinobu Yasuo; Marco Koch; Helmut Schmidt; Simone Ziebell; Joerg Bojunga; Gerd Geisslinger; Horst-Werner Korf (Cell and Tissue Research, 2010)

Predation has a greater impact in less productive environments: variation in roe deer, Capreolus capreolus , population density across Europe - Claudia Melis; Bogumiła Jędrzejewska; Marco Apollonio; Kamil A. Bartoń; Włodzimierz Jędrzejewski; John D.C. Linnell; Ilpo Kojola; Josip Kusak; Miha Adamic; Simone Ciuti; Ivan Delehan; Ihor Dykyy; et al. (Global Ecology and Biogeography, 2009)
Aim We aimed to describe the large‐scale patterns in population density of roe deer Caprelous capreolus in Europe and to determine the factors shaping variation in their abundance. Location Europe. Methods We collated data on roe deer population density from 72 localities spanning 25° latitude and 48° longitude and analysed them in relation to a range of environmental factors: vegetation productivity (approximated by the fraction of photosynthetically active radiation) and forest cover as proxies for food supply, winter severity, summer drought and presence or absence of large predators (wolf, Canis lupus , and Eurasian lynx, Lynx lynx ), hunter harvest and a competitor (red deer, Cervus elaphus ). Results Roe deer abundance increased with the overall productivity of vegetation cover and with lower forest cover (sparser forest cover means that a higher proportion of overall plant productivity is allocated to ground vegetation and thus is available to roe deer). The effect of large predators was relatively weak in highly productive environments and in regions with mild climate, but increased markedly in regions with low vegetation productivity and harsh winters. Other potentially limiting factors (hunting, summer drought and competition with red deer) had no significant impact on roe deer abundance. Main conclusions The analyses revealed the combined effect of bottom‐up and top‐down control on roe deer: on a biogeographical scale, population abundance of roe deer has been shaped by food‐related factors and large predators, with additive effects of the two species of predators. The results have implications for management of roe deer populations in Europe. First, an increase in roe deer abundance can be expected as environmental productivity increases due to climate change. Secondly, recovery plans for large carnivores should take environmental productivity and winter severity into account when predicting their impact on prey.

Evidence for a perception of prosodic cues in bat communication: contact call classification by Megaderma lyra - Simone Janßen; Sabine Schmidt (Journal of Comparative Physiology A, 2009)

Nitrogen and metals in two regions in Central Europe: Significant differences in accumulation in mosses due to land use? - Winfried Schröder; Inga Hornsmann; Roland Pesch; Gunther Schmidt; Bernd Markert; Stefan Fränzle; Simone Wünschmann; Heike Heidenreich (Environmental Monitoring and Assessment, 2007)

Assessment of fish health status in four Swiss rivers showing a decline of brown trout catches - Simone Zimmerli; Daniel Bernet; Patricia Burkhardt-Holm; Heike Schmidt-Posthaus; Pascal Vonlanthen; Thomas Wahli; Helmut Segner (Aquatic Sciences, 2007)

Hormonal activity of combinations of genistein, bisphenol A and 17β-estradiol in the female Wistar rat - Simone Schmidt; Gisela H. Degen; Jan Seibel; Torsten Hertrampf; Günter Vollmer; Patrick Diel (Archives of Toxicology, 2006)

Iron distribution in three central Amazon tree species from whitewater-inundation areas (várzea) subjected to different iron regimes - Oliviero De Simone; Ewald Müller; Wolfgang J. Junk; Kerstin Richau; Wolfgang Schmidt (Trees, 2003)